From irony to despair: An “organic” model of resistance strategies in the era of surveillance and big data - Jaseff Raziel Yauri Miranda; Dafne Calvo; Maria Iranzo-Cabrera (Anàlisi: Quaderns de Comunicació i Cultura)
In an era of surveillance and big data, we aim to interpret resistance strategies and tactics beyond the individuals and groups that employ them. We propose a model for interpreting resistance, covering power asymmetries between different actors, and incorporating social justice claims. The model sets out four main strategies: a) ironic, based on communication and aesthetics; b) deliberative, based on cooperation; c) agonistic, based on confrontation; and d) despairing, based on open and direct conflict provoked by the discontent of a multitude assembled as a unified actor. The model moves from individual reflections and initiatives supporting democratic values, to the collective – and sometimes violent – demand for a new social order. There are two scales where this power of resistance can operate: the micro-macro level of politics; and the exceptional or generative level of social change, allowing surveillance studies to be linked to other social fields. Our results indicate that, rather than being isolated tactics, the four strategies display an organic and ecological sense of interdependence. When the four strategies are maximized at any given time, the conditions are created for a ‘perfect’ situation of resistance to bring out deep changes in many sociopolitical orders.